Clinical reconstruction of metal-plastic crowns as a component of teeth splinting in patients with generalized periodontitis in a stage of remission - Ishchenko, P.; Borisenko, A.; Vilchik, G.; Machnyova, A. (Actual Dentistry, 2018)
Summary. The article describes the variants of non-removable splinting by orthopedic constructions in patients with periodontal disease. Characteristics of tsplints, their advantages and disadvantages are presented. The problems of supporting teeth overloading by orthopedic constructions and solution techniques with the help of orthopedic metal-plastic splints and removable prostheses are described. Clinical technique of reconstruction of worn metal-plastic splint-prosthesis is described in details in the article. Key words: periodontitis, splint, metal-plastic construction.